Effects of 24-week Polarized Training vs. Threshold Training in Obese Male Adults - D’Alleva, Mattia; Giovanelli, Nicola; Graniero, Francesco; Billat, Veronique Louise; Fiori, Federica; Marinoni, Michela; Parpinel, Maria; Lazzer, Stefano (International Journal of Sports Medicine, 2024)
The combination of high volume of moderate-intensity continuous training with a low volume of high-intensity interval training improved body composition and physical capacities in individuals with obesity. However, polarized training (POL) has never been used in adult men with obesity. Thus, the purpose of this study was to investigate changes in body composition and physical capacities induced by a 24-week POL or threshold (THR) program in obese male adults. Twenty male patients (mean age 39.8±6.3 yrs; mean body mass index [BMI] 31.6±2.7 kg∙m−2) participated in this study (n: 10 POL, n: 10 THR). After 24-week, body mass (BM) and fat mass (FM) decreased by -3.20±3.10 kg (P<0.05) and -3.80±2.80 kg (P<0.05), respectively, similarly in both groups. Maximal oxygen uptake (  ̇VO2max) and ̇VO2 at respiratory compensation point (RCP) increased in the POL group (+8.5±12.2 and+9.0±17.0%, P<0.05) and in the THR group (+4.24±8.64 and+4.0±6.70%, P<0.05), as well   ̇VO2 at gas exchange threshold (GET) increased similarly in both groups (+12.8±12.0%, P<0.05). POL and THR were equally effective in improving body composition and physical capacities in obese subjects. Future studies are needed to determine whether adherence to the training program can be improved by adding a running competition compared with a group without competition at the end of the training program.
Keywords: body composition; endurance; obesity; polarized training; threshold training